Илюзията като методика в обучението по литература - Dilovski, Vladimir (Lyuboslovie, 2024)
This article studies the illusory nature of artistic fictionality and the ways in which this unreality affects reality. Examples are given of how the “method of deception” carries out the author’s intention from the time of Sophocles to the present day. The deliberate deception of the reader is a manifestation of the game, which is an aspect of the essence of the literary text, but it also provokes thinking, which reflects on a person’s behavior in reality. The short story “Kosachi/Mowers” by Elin Pelin presents the role of the imaginary, the illusory as an escape from the “bad” truths, but also shows how it can become a motive for a decisive action. The second aspect of the research is related to the methodology of teaching literature at school and how the artistic illusion supports the personality formation with role models. “Antigone” (Sophocles), “Po zhitsata/ On the Wire” (Y. Yovkov), “Hamlet” (Shakespeare), “Noev kovcheg/ Noah’s Ark” (Y. Radichkov), etc. studied at primary and high school present various manifestations of artistic illusion and its impact on the student’s consciousness at the very important stage of their lives when their values are formed. The question about the role of artificial intelligence in teaching literature is raised but its answer is not clear-cut yet. The interpretation of the literary text is a subjective act expressing the understanding of the author’s messages, and it cannot be replaced and displaced by the standardized and clichéd “utterances” of the AI embedded in its databases. The illusory nature of machine intelligence cripples the discourse in which the communicative process takes place, because it displaces the main thing in it – human uniqueness and originality.